2023
DOI: 10.1097/qad.0000000000003497
|View full text |Cite
|
Sign up to set email alerts
|

Smallpox vaccine acceptability among French men having sex with men living with HIV in settings of monkeypox outbreak

Abstract: Smallpox vaccine acceptability among French men having sex with men living with HIV in settings of monkeypox outbreak Monkeypox virus (MPX) is an orthopoxvirus discovered in Democratic Republic of Congo in 1970. Clinical presentation associates skin lesions in the anogenital and perioral regions, along with systemic symptoms such as fever, myalgia, or headache [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…With more than 60% of participants receiving the vaccine or planning to get vaccinated, our findings are on the lower end of other studies that also reported mpox vaccine uptake (or willingness to vaccinate) ranging from 51% to 95% among at-risk populations [ 10 , 23 , 24 , 25 , 26 , 27 ]. In a study of transgender people and gay and bisexual men who have sex with men (T/GBM) from an STI clinic in British Columbia, 66% of participants identifying as T/GBM had been vaccinated, and being unvaccinated was more common in participants who identified as bisexual or heteroflexible/mostly straight [ 26 ].…”
Section: Discussioncontrasting
confidence: 69%
“…With more than 60% of participants receiving the vaccine or planning to get vaccinated, our findings are on the lower end of other studies that also reported mpox vaccine uptake (or willingness to vaccinate) ranging from 51% to 95% among at-risk populations [ 10 , 23 , 24 , 25 , 26 , 27 ]. In a study of transgender people and gay and bisexual men who have sex with men (T/GBM) from an STI clinic in British Columbia, 66% of participants identifying as T/GBM had been vaccinated, and being unvaccinated was more common in participants who identified as bisexual or heteroflexible/mostly straight [ 26 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Moreover, sociodemographic factors such as age, gender, geographic area of residence, fear of adverse effects, or distrust of medical personnel and the health care system may influence vaccination decision making [ 12 , 15 ]. A number of studies have been published evaluating people’s willingness to accept MpoxVax, including both the general population [ 16 ] and high-risk individuals [ 8 , 17 , 18 , 19 ]; but, with the exception of a few recent reports focusing on MpoxVax uptake in a small number of subjects [ 20 , 21 , 22 ], data on its determinants are lacking.…”
Section: Introductionmentioning
confidence: 99%